PIPNet: A Deep Convolutional Neural Network for Multibaseline InSAR Phase Unwrapping Based on Pure Integer Programming - Hui Liu; Ke Zheng; Changwei Miao; Xuemei Liu; Xianlin Liu; Lin Li; Yongguang Zhang; Longhai Xiong (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing)
Multibaseline (MB) phase unwrapping (PU), as the core step in MB InSAR, breaks the limitation of phase continuity assumption. However, it still suffers from insufficient noise robustness and low unwrapping efficiency. This article transforms the MB PU problem into pure integer programming (PIP) problem and innovates a deep convolutional neural network named PIPNet to solve PU problem. This PIPNet is built on the U-Net framework, incorporating Transformer modules, upsampling, and dense connections mechanisms to achieve powerful feature extraction capabilities. Interferometric phase, fringe frequency, and intercept data are input into multiports of PIPNet, with multisource features fused in the encoding–decoding stages to collectively act on PU. Then, we innovatively designed a new joint loss function and PIP constraints to guide the iterative optimization of model parameters. The attention mechanism enhances the model ability to disentangle interferometric phase details. Finally, the trained model can achieve real-time and accurate calculation of phase ambiguity number. Theoretical analysis and two experimental results indicate that PIPNet-PU has much lower execution time than MCF, cluster analysis, and two-stage programming approach algorithms, and the second-best unwrapping accuracy for short-baseline interferogram and the best unwrapping ability for long-baseline interferogram. PIPNet-PU can achieve good unwrapping effects even in areas with abrupt topographic change and dense interferometric fringes.